Real-time gene expression analysis in human xenografts for evaluation of histone deacetylase inhibitors - Beliën, Ann; De Schepper, Stefanie; Floren, Wim; Janssens, Boud; Mariën, Ann; King, Peter; Van Dun, Jacky; Andries, Luc; Voeten, Jan; Bijnens, Luc; Janicot, Michel; Arts, Janine (Molecular cancer therapeutics, 2006)
Real-time analysis of gene expression in experimental tumor models represents a major tool to document disease biology and evaluate disease treatment. However, monitoring gene regulation in vivo still is an emerging field, and thus far it has not been linked to long-term tumor growth and disease outcome. In this report, we describe the development and validation of a fluorescence-based gene expression model driven by the promoter of the cyclin-dependent kinase inhibitor p21 waf1,cip1 . The latter is a key regulator of tumor cell proliferation and a major determinant in the response to many anticancer agents such as histone deacetylase inhibitors. In response to histone deacetylase inhibitors, induction of fluorescence in A2780 ovarian tumors could be monitored in living mice in a noninvasive real-time manner using whole-body imaging. Single p.o. administration of the histone deacetylase inhibitor MS-275 significantly induces tumor fluorescence in a time- and dose-dependent manner, which accurately predicted long-term antitumoral efficacy in individual mice following extended treatment. These findings illustrate that this technology allows monitoring of the biological response induced by treatment with histone deacetylase inhibitors. In addition to providing experimental pharmacokinetic/pharmacodynamic markers for investigational drugs, this model provides insight into the kinetics of in vivo regulation of transcription, which plays a key role in causing and maintaining the uncontrolled proliferation of tumor tissue. [Mol Cancer Ther 2006;5(9):2317–24]